LANGUAGE LEARNING IN POST CONFLICT SOCIETIES ("Conference on Universal Science Research 2023", 2024)
Language learning plays a key role in rebuilding post-conflict societies by promoting understanding and helping people reconnect. This article investigates how language education can help communities heal after conflict. It looks at the importance of using language to bridge divides, address trauma, and foster peace. It also discusses challenges and examples of successful programs.